1901 Ariz. Sess. Laws 1251 - (:unkn) unknown (My University, 1901)
§ 382: Prohibited the concealed carrying of any pistol or other firearm, dirk, dagger, slungshot, sword cane, spear, brass knuckles, Bowie knife (or any kind of knife, except a pocket knife not manufactured for offensive or defensive use). Exempted peace officers in discharge of official duties. Punishable by a fine of $25-100 and forfeiture of the weapon.
Keywords: CARRY - CONCEALED